Not a race to humanism - Canham, Hugo (PINS-Psychology in Society, 2018)
[Book Revie] Erasmus, Zimitri (2017) Race otherwise: Forging a new Humanism for South Africa. Johannesburg: Wits University Press. ISBN 978-1-77614-058-9 pbk. Pages ix + 171 In 2017, Zimitri Erasmus and Wits University Press quietly published Race otherwise: Forging a new humanism for South Africa. This book follows her 2001 edited book titled Coloured by history, shaped by place: New perspectives on Coloured identities in Cape Town. In the 16 years in between the two books, Erasmus has spent a considerable amount of time and thought developing her ideas and convictions on the fallibility of race. In today’s talk, she has been a #racemustfall activist. She joins scholars such as Gerhard Maré (2014) who has pointed out that race thinking has become more entrenched in the post-apartheid political order and in everyday life. These scholars argue that the anti-apartheid impetus towards non-racialism has been sacrificed at the altar of redress legislation such as the Employment Equity Act No.55 of 1998 and its implications for re-inscribing race talk and race identification. In some ways then, race has crystalised and become a steady material reality in post-apartheid South Africa. In her latest publication, Erasmus expands on these arguments but presents readers with arguments and tools for thinking outside of race. In the tradition of Sylvia Wynter, her alternative and way out of the race conundrum is a new humanism.